Perception Investigation Based on the Commuting Cost Model - Nindyo Cahyo Kresnanto; Wika Harisa Putri; Rini Raharti; Muhamad Willdan; Raihan Iqbal Ramadhan (Applied Research on Civil Engineering and Environment (ARCEE), 2023)
Travel expenses are a significant factor in transportation planning. In addition to the other aspect, travel time, the community considers expense as the necessary element in deciding which mode the communities should take. However, there is a gap between the actual transport expense and the commuter's perception. Thus, comprehensive knowledge is urgently needed particularly to be seen as a major variable in transportation planning that sided with underprivileged groups of transport poverty. The study focused on describing the correlation between income and commuting transportation expenses. The analysis was carried out using two methods. The first method is a descriptive analysis used to provide insight into the patterns and characteristics of the data obtained from interviews with 421 respondents. The second method is regression analysis (linear and nonlinear) to explain the relation pattern between the dependent (commuting transportation expenses) and independent (income) variables. The study's findings demonstrate that transportation expenses follow a negative polynomial regression pattern on income, further implying that the percentage of transportation expenses in low-income communities is significantly higher than those in high-income communities.